Традиційна загадка і варіанти її відгадок - Сикимич, Б. (Народна творчість та етнологія, 2012)
The author reviews an issue of usage of the terms «folk riddle» and «traditional riddle» to distinguish the modern riddles and solutions similar to them which likewise have all the features of folkloric text and function in the modern folkloric context. The special attention is paid to the importance of the traditional riddles for determining the cultural-cognitive categories due to the fact that modeling of them depends on the community’s conceptual system. Contents of the traditional riddles covered the great territories or recorded in the different variants may assist to appreciate the local peculiarities on both the linguistic level and the level of the text’s structure. The author accepts a conception of D. Ben-Amos under which the suggestions of the conventional solutions of traditional riddles in modern society are not something special and consequently instead of ordinary well-known answers to the riddles usually proposed are new ingenious and humorous solutions. There is an analysis of the popular riddle (in Beograd urban culture) about the «teeth»: «The white pullets look out from under the eaves» used in the broadcasts of local FM station B-92 during the health defense campaign.